(untitled) (Global Journal of Medical Research, 2022)
As of march 2022, the World health Organisation stated that the COVID-19 pandemic has triggered an immense 25% increase in the global prevalence of anxiety and depression (WHO, 2022). It is important that precautions are taken to protect the mental health of individuals affected by the pandemic and more specifically the youth. This paper aims to investigate the psychological effects of the pandemic on adolescents and it also sheds light on the coping mechanisms used by these individuals. By integrating results from various research a general conclusion was made that the COVID-19 pandemic has altered the daily activities of adolescents, causing stress, depression, harmful lifestyle engagements and even self-injury.